The challenges of educational systems adopted in Modular High School in the countryside at Rui Barbosa School, Medicilândia, Pará - Alcinei da Silva Araujo; Fabíola Aparecida Ferreira Damacena; Carla Giovana Souza Rocha (Universidade Federal do Norte do Tocantins, 2021)
The research aims to reflect on the Modular Teaching Organization System (SOME) based on a case study at Escola Rui Barbosa, Medicilândia, Pará. Focusing on supply and operation, in addition to understanding the process of acceptance of the Interactive Educational System (SEI) by the community. The approach was quali-quantitative, with interviews, collection and processing of secondary data and documentary research. Secondary education in this community is the result of collective social struggle, with an increase in the number of enrollments from 2003 to 2019, as well as a decrease in the number of dropouts. Despite the challenges of ensuring the supply of subjects, teachers and infrastructure, SOME was defended by the school community for guaranteeing access to secondary education in the countryside. The local community does not support replacement by the SEI presented by the state government as a pilot proposal, considering that there will be a loss in the quality of education and a devaluation of teachers. Popular participation in the definition of public educational policies is not a priority for public agents, who continue to define them without discussion with society.